Shelf-life Extension of Refrigerated Soft Shell Mud Crab (Scylla serrata Forskal) by Ozone Water and Storage under Air and Modified Atmosphere Packaging - Nathapol Phapinyo,; Tawirat Chaowalit,; Aiyakarn Tanpipattanakul,; Kijja Sooknet,; Aekarat Kumthong,; Wanchai Worawattanamateekul,; Jim P. Smith, (Agriculture and Natural Resources, 2007)
The effects of ozone water combined with modified atmosphere packaging on the refrigerated storage quality of soft shell mud crab at 4±0.5 °C were investigated. Soft shell mud crab stored under modified atmosphere packaging and vacuum had lower microbial counts compared with that of mud crab stored in an aerobic package (p<0.05). The odor and overall acceptability were acceptable for the soft shell mud crabs packaged under 80%CO2+20%N2 and vacuum throughout the storage period of 11 days. Microbial changes in all samples were generally in agreement with sensory panel evaluations. The shelf life of soft shell mud crab soaked in 1.0 ppm for 20 min and packaged under 80%CO2+20%N2 and vacuum was extended to at least 11 days at 4±0.5 °C. The shelf life of soft shell mud crab soaked in water and aerobically packaged was 3 days.